Pharmacoeconomic analysis of vemurafenib and dabrafenib use in patients with inoperable or metastatic melanoma with BRAF V600 mutation - A. S. Kolbin; A. A. Kurylev; Yu. E. Balykina; M. A. Proskurin (Izdatelstvo OKI, 2018)
Aim. To perform health-economic evaluation of vemurafenib in comparison to dabrafenib in patients with metastatic or unresectable melanoma with BRAF V600 mutation in Russia from the healthcare system perspective. Materials and methods. Mathematical modelling and cost effectiveness analysis with cost-effectiveness ratio (CER) calculation were used. If costs and effectiveness of one drug are higher comparing to another incremental cost-effectiveness ration is calculated. We accounted for following direct medical costs: vemurafenib and dabrafenib, diagnostic procedures, hospital stay, outpatient visits, BRAF mutation test, adverse events correction. Two heath technologies were evaluated: vemurafenib 960 mg BID, dabrafenib 150 mg BID. Results. In patients with metastatic or unresectable melanoma vemurafenib and dabrafenib have comparative effectiveness, but vemurafenib total costs were by 3,7% lower. Vemurafenib CER was by 7% and 18% lower comparing to dabrafenib when median and mean PFS, respectively, are used as effectiveness criteria. Conclusions. The study shows vemurafenib to be a cost-effective strategy. The cost of drug has the maximum influence on the study results.